Cohesion and Coherence of Narrative Essays of Madagascar Students of Indonesian Language for Foreign Speakers (BIPA) at UPTP2B Sebelas Maret University - Basuki Rachmat Sinaga; Andayani Andayani; Sahid Teguh Widodo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aimed to describe the use of the form of cohesion and coherence of narrative essay of Madagascar students of Indonesian Language for Foreign Speaker (BIPA) at Language Center Sebelas Maret University. The method used was descriptive qualitative. The researcher collected the data by giving assignments to the students. Then, the researcher classified the findings with the techniques of reading, listening, and writing. The results obtained in the form of cohesion were: 1) grammatical cohesion consisted of reference, substitution, ellipsis, and conjunction; 2) lexical cohesion consisted of repetition, synonym, and collocation. In the form of coherence, the students were able to express their writing in a simple way to be able to be understood by the readers.